An Antifungal Antibiotic Purified from Bacillus megaterium KL39, a Biocontrol Agent of Red-Pepper Phytophthora-Blight Disease - Jung, H.K. (Yeungnam University, Gyeongsan, Republic of Korea); Kim, S.D. (Yeungnam University, Gyeongsan, Republic of Korea), E-mail: sdkim@yumail.ac.kr (Journal of microbiology and biotechnology, 2005)
Bacillus megaterium KL39, an antibiotic-producing plant growth promoting rhizobacterium (PGPR), was selected from soil. The antifungal antibiotic, denoted KL39, was purified from culture filtrate by column chromatography using Dion HP-20, Silica gel, Sephadex LH-20, and prep-HPLC. Thin layer chromatography, employing the solvent system of ethanol:ammonia:water=8:1:1, showed the R∧f value of 0.32. The antibiotic KL39 showed a negative reaction with ninhydrin solution, positive with iodine vapor, and also positive with Ehrlich reagent.